An Examination of the Relationship between CSR Disclosure and Financial Performance: The Case of Polish Banks - Łukasz Matuszak; Ewa Różańska (Journal of Accounting and Management Information Systems (JAMIS), 2017)
The purpose of this study is twofold. First, this study investigates the trends of corporate social responsibility (CSR) reporting and financial performance (FP) in commercial banks in Poland. Second, this study examines the impact of the CSR disclosure of the banks on their financial performance (ROA, ROE, NIM). Sample consists of 18 banks. The data from annual reports for the period of 8 years (2008 – 2015) were both hand collected and obtained from Notoria Servis Database. A content analysis is used to measure the level of CSR disclosures and a panel data analysis is employed to examine the CSR-FP relationship. Software: GRETL. Two key findings: (1) Positive relationship between banks' CSR disclosures and their profitability measured by ROA and ROE. However, the relationship between banks' CSR disclosures and NIM is negative. Statistical analysis did not report any significant effect of CSR activities on ROA, ROE and NIM ratios. (2) Banks' CSR activities are not dominant predictor of their profitability as compared with control variables. To our best knowledge this research is the first quantitative analysis regarding banking sector in Poland. Further, this study was conducted in emerging market with different socio-economic context and regulations compared to developed market. The findings contribute to and increase the understanding of the relationship between CSR disclosures and FP. Finally, this study has important implications for policy makers, managers, investors, and others.
Keywords: C33; G21; G32; M14; M41; 650; corporate social responsibility; financial performance; polish banks